Biodegradability of wastewater determines microbial assembly mechanisms in full-scale wastewater treatment plants - Zhang, Bing; Ning, Daliang; Yang, Yunfeng; Van Nostrand, Joy D.; Zhou, Jizhong; Wen, Xianghua (Water research (Oxford), 2020)
Wastewater treatment plants (WWTPs) are critical for maintaining sustainable development in modern societies, wherein microbial populations residing in activated sludge (AS) are responsible for the removal of pollutants from wastewater. The biodegradability [biological oxygen demand/chemical oxygen demand (B/C ratio)] of influent, as a measure of the degree of available energy and toxicity to microorganisms in AS, has been hypothesized to drive AS microbial community assembly. However, the validity of this hypothesis has not been tested in full-scale WWTPs. In this study, we assessed the pollutant removal loads, the microbial community diversity, the relative importance of deterministic and stochastic assembly processes, and bio-interactions within the communities by analyzing 195 AS samples comprising nearly 5 000 000 16S rRNA sequences. Our results indicate that the effects of B/C ratio on pollutant removal loads can be perfectly reflected through biological properties, implying that B/C ratio determined WWTPs performance through affecting microbial community. Very low and/or very high B/C ratios result in low microbial diversity, strong stochastic processes, and large, complex networks, leading to low pollutant removal load of treatment. A B/C ratio of around 0.5 was optimal for system stability and efficiency. Based on the results of this study, the authors propose using the B/C ratio as an indispensable index to assess system performance and to provide an indicator of an impending process upset before function deteriorates significantly. This study provides a specific measure that can be used to evaluate strategies for process optimization and operation of WWTPs. [Display omitted] •Biodegradability of wastewater affected pollutant removal loads of WWTPs.•Biodegradability of wastewater determined microbial assembly mechanisms in WWTPs.•A BOD/COD ratio of around 0.5 was optimal for WWTP stability and efficiency.